Evaluating the precariousness of coral recovery when coral and macroalgae are alternative basins of attraction. Issue Volume 67:Issue S1(2022)Special issue (14th September 2021) - Schmitt, Russell J.; Holbrook, Sally J.; Brooks, Andrew J.; Adam, Thomas C.
Abstract: When coral and macroalgae are alternative attractors, the trajectory of the benthic community following a major disturbance is shaped in part by whether herbivores keep macroalgae suppressed, leaving reef surfaces in a state suitable for coral colonization. Because macroalgae tend to colonize much faster than coral, an important issue is how close ambient herbivory is to the level where control of macroalgae is lost, that is, the precariousness of the coral‐invasible state relative to the switch‐point to macroalgae. In Moorea, French Polynesia, reefs dominated by the macroalga Turbinaria ornata remained so for multiple population turnovers, whereas reefs where Turbinaria was removed by a simulated pulse disturbance remained free of macroalgae throughout the 5‐yr study. A field experiment revealed that macroalgae was unable to proliferate on disturbed reefs until ambient herbivory was reduced by more than 50%. Low precariousness of the coral‐invasible state facilitated a gradual transition to a coral community because it allowed sufficient time for coral to repopulate. Accumulation of coral on disturbed reefs was 3.5 times greater than on undisturbed, Turbinaria ‐dominated reefs. Long‐term persistence of the coral‐invasible state was facilitated by high abundances of grazing herbivores that prevent the establishment of macroalgae, whereas persistence of the Turbinaria ‐dominated state reflected the scarcity of browsing herbivores that consume mature macroalgae. By revealing processes that foster bistability of coral and macroalgae states, our work helps explain the rich dynamical behavior exhibited by coral reef communities in Moorea and elsewhere.